The Common core companion : the standards decoded, grades 9-12--what they say, what they mean, how to teach them - Burke, Jim, 1961- (Thousand Oaks, California : Corwin Press, 2013)
Burke, a high school English teacher and author, helps high school teachers, administrators, and education students understand the Common Core State Standards (CCSS) in English language arts for reading, writing, speaking and listening, and language, what each says and means, and how to apply them in daily practice across English language arts, history/social studies, science, and technical subjects. Each section includes a restatement of the official anchor standards as they appear in the CCSS document, a translation of each standard and its objectives, highlights of differences between grades, standards for each discipline, comprehension questions to help students master thinking skills, synopses of the standards, specific teaching techniques for all subjects, and a glossary of academic vocabulary. --Publishers Description
Quick reference : Common Core State Standards, 6-12 English Language Arts -- Quick reference : Common Core State Standards, 6-12 English Language Arts in History/Social Studies, Science, and Technical Subjects -- The Complete Common Core State Standards decoded -- Reading. Key ideas and details ; Craft and structure ; Integration of knowledge and ideas ; Range of reading and level of text complexity -- Writing. Text types and purposes ; Production and distribution of writing ; Research to build and present knowledge ; Range of writing -- Speaking and listening. Comprehension and collaboration ; Presentation of knowledge and ideas -- Language. Conventions of standard English ; Knowledge of language ; Vocabulary acquisition and use.
Includes bibliographical references (pages 217-219).
Keywords: Language arts (Secondary) -- United States; Language arts -- Standards -- United States